Reproductive resilience but not root architecture underpins yield improvement under drought in maize. (25th May 2021) - Messina, Carlos; McDonald, Dan; Poffenbarger, Hanna; Clark, Randy; Salinas, Andrea; Fang, Yinan; Gho, Carla; Tang, Tom; Graham, Geoff; Hammer, Graeme L; Cooper, Mark
Abstract: Because plants capture water and nutrients through roots, it was proposed that changes in root systems architecture (RSA) might underpin the 3-fold increase in maize ( Zea mays L.) grain yield over the last century. Here we show that both RSA and yield have changed with decades of maize breeding, but not the crop water uptake. Results from X-ray phenotyping in controlled environments showed that single cross (SX) hybrids have smaller root systems than double cross (DX) hybrids for root diameters between 2465 µm and 181µm ( P <0.05). Soil water extraction measured under field conditions ranged between 2.6 mm d –1 and 2.9 mm d –1 but were not significantly different between SX and DX hybrids. Yield and yield components were higher for SX than DX hybrids across densities and irrigation ( P <0.001). Taken together, the results suggest that changes in RSA were not the cause of increased water uptake but an adaptation to high-density stands used in modern agriculture. This adaptation may have contributed to shift in resource allocation to the ear and indirectly improved reproductive resilience. Advances in root physiology and phenotyping can create opportunities to maintain long-term genetic gain in maize, but a shift from ideotype to crop and production system thinking will be required. Abstract : Emerging opportunity to continue long-term genetic gain in maize yield in the US corn belt by improving the balance between canopy, root, and reproductive growth and development.